SOLAR-FORCED 2600 BP AND LITTLE ICE AGE HIGHSTANDS OF THE CASPIAN SEA - S. B. Kroonenberg; G. M. Abdurakhmanov; E. N. Badyukova; K. van der Borg; A. Kalashnikov; N. S. Kasimov; G. I. Rychagov; A. A. Svitoch; H. B. Vonhof; F. P. Wesselingh (Юг России: экология, развитие)
The researches combining a social, economic and ecological content, find out a generality of appendix area and global purpose. This purpose image is hidden behind the term sustainable development". These restrictions are presented as the multiplicative index of the development. This index is reflecting an information balance of a territory.The level of the Caspian Sea, the largest inland sea in the world, has fluctuated capriciously in history, with amplitudes up to 3 m in the last century, to 25m in the last millennium, and to over 150m since the Last Glacial. The results suggest that the last major highstands occurred around 2600 BP and in the Little Ice Age and coincide with global cooling events associated with minima in solar activity. This suggests that millennial precipitation changes in the Volga River drainage basin are also forced by solar activity.